Analiza Stateczności Zamkniętej Ortotropowej Powłoki Walcowej pod Działaniem Ciśnienia Hydrostatycznego - Nowak, Z. (Engineering Transactions, 1965)
The object of the paper a is a linear and nonlinear stability analysis of a thin-walled, closed, circularly cylindrical shallow shell showing natural orthotropy and subjected to a constant pressure. In contrast with other papers it is assumed that the edges of the shell are clamped and cannot be displaced radially. Making use of the Ritz-Timoshenko method the upper and lower critical pressure are determined.The numerical example concerns an isotropic shell. A comparative analysis of results is given for the shell above and another shell, of the same geometric and elastic properties, but resting on simple supports.